2013
DOI: 10.1088/1367-2630/15/4/043017
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of nanodiamond nitrogen–vacancy centers for spontaneous emission control experiments

Abstract: Nitrogen-vacancy (NV) centers in diamond are generally recognized as highly promising as indefinitely stable highly efficient single-photon sources. We report an experimental quantification of the brightness, radiative decay rate, nonradiative decay rate and quantum efficiency of single NV centers in diamond nanocrystals. Our experiments show that the commonly observed large spread in fluorescence decay rates of NV centers in nanodiamond is inconsistent with the common explanation of large nanophotonic mode-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 76 publications
(209 reference statements)
16
88
0
Order By: Relevance
“…The result for the smallest nanodiamonds is partially supported by fitting the measured secondorder correlation function of a NV defect with that of a three-level system [16]. Interestingly, it was shown in [15] that the wide IQE distribution is due to a variation in both the radiative as well as the non-radiative decay rates among the different nanocrystals. This is surprising since the non-radiative rates are not of electromagnetic origin, therefore not sensitive to the local density of optical states (LDOS) and therefore the variation was due to intrinsic properties of the nanocrystals.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The result for the smallest nanodiamonds is partially supported by fitting the measured secondorder correlation function of a NV defect with that of a three-level system [16]. Interestingly, it was shown in [15] that the wide IQE distribution is due to a variation in both the radiative as well as the non-radiative decay rates among the different nanocrystals. This is surprising since the non-radiative rates are not of electromagnetic origin, therefore not sensitive to the local density of optical states (LDOS) and therefore the variation was due to intrinsic properties of the nanocrystals.…”
Section: Introductionmentioning
confidence: 74%
“…Mohtashami and Koenderink [15] considered diamond nanocrystals containing native single NV defects, and found that for NV defects in 25-nm nanodiamonds the IQE is distributed between 0 and 20%, while for 100-nm nanodiamonds the IQE has an even larger distribution in the range 10-90%. The result for the smallest nanodiamonds is partially supported by fitting the measured secondorder correlation function of a NV defect with that of a three-level system [16].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, careful control of strain and crystalline quality seems necessary to obtain high QE: QE in the range of only 25-60% was found in ion-damaged diamond (H-implantation, fluence F = 1 × 10 15 cm −2 corresponding to an estimated induced vacancy density d = 60 ppm, [58]). NV centers in 25-nm nanodiamonds even may show QE < 20% [59].…”
Section: Photochromism Quantum Efficiencies and Coherence Timementioning
confidence: 99%
“…Sekatskii and co-workers [122] reported on unsuccessful experiments on FRET transfer between a scanning NV and a dye molecule, despite previous demonstration of FRET to dye molecules covalently bonded to NDs [8]. This finding might relate to a varying quantum efficiency (QE) for NV centers in NDs [59], the need for accurate control of the ND surface (graphite layers), as well as to large stand-off distances when attaching an ND to a scanning probe tip. These issues may be addressable in the future using scanning probe devices sculpted out of single-crystal diamond [41,61].…”
Section: Near-field Microscopy With Nv Centersmentioning
confidence: 99%
“…While the quantum efficiency of terrylene in p-terphenyl is known to reach values beyond 95% [16], our measurements reveal a substantial inhomogeneity that leads to a distribution of the emitted powers. This behavior is also common for other solid-state systems such as color centers in diamond [8]. Thus, to achieve the lowest loss level, we performed our experiments on molecules with a high emission rate.…”
mentioning
confidence: 96%